2006
DOI: 10.1016/j.bone.2006.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates suppress periosteal osteoblast activity independently of resorption in rat femur and tibia

Abstract: Recent studies demonstrate that bisphosphonates suppress bone resorption by leading to apoptosis of the osteoclast and inhibiting the differentiation to mature osteoclasts. The influence of bisphosphonates on bone formation is unknown, although it has been hypothesized that bisphosphonates inhibit osteoblast apoptosis and stimulate osteoblast proliferation and differentiation in vitro, leading to increased bone formation. The purpose of this study was to investigate the effect of bisphosphonates on bone format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 42 publications
4
57
1
1
Order By: Relevance
“…As this periosteal modeling should be independent of osteoclast activity, this may indicate a direct effect of bisphosphonates on osteoblast activity. 31 Most bisphosphonate compound is bound to bone mineral and only osteoclasts are able to release and take up bound bisphosphonates. 32 The effects of bisphosphonates on osteoclast function are therefore likely to be more prominent than effects of transiently unbound bisphosphonates on other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…As this periosteal modeling should be independent of osteoclast activity, this may indicate a direct effect of bisphosphonates on osteoblast activity. 31 Most bisphosphonate compound is bound to bone mineral and only osteoclasts are able to release and take up bound bisphosphonates. 32 The effects of bisphosphonates on osteoclast function are therefore likely to be more prominent than effects of transiently unbound bisphosphonates on other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…After depletion of pre-osteoclasts, alendronate had no effect on gene expression, indicating that this is an indirect effect. Iwata et al (2006) have shown that bisphosphonates suppress bone formation. Intracortical remodeling of the alveolar portion of the mandible was significantly suppressed by zoledronate treatment (Kubek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(7,(19)(20)(21) Emerging evidence suggests that bisphosphonates may affect osteoblasts and osteocytes directly, with some studies showing intereference with apoptosis, resulting in prolonged bone formation, (39,40) whereas other studies suggest bisphosphonate toxicity on osteoblasts. (16,41,42) Additionally, the interaction between bisphosphonates and nonbone cells, such as T cells, has been described. (43) Therefore, the development of sensitive techniques to assess local bisphosphonate concentration at relevant skeletal sites would advance understanding of the interplay between bisphosphonates and bone cells in vivo.…”
Section: Discussionmentioning
confidence: 99%